Філософське осмислення свята як феномену культури - Поправко, Ольга Вікторівна; Поправко, Ольга Викторовна; Popravko, Olha (My University, 2016)
UK: Стаття присвячена осмисленню свята як феномену культури. Проаналізовано існуючі наукові концепції свята. На основі аналізу автор побудувала теоретичну модель свята як уособлення ідеального світу, враховуючи всі сутнісні характеристики, які від- різняють його від буденного життя. Сутність свята розкрита в контексті його співвіднесення з буднями. Особлива увага зосереджена на висвітленні структурних компонентів свята, які підтримують його статус в культурному бутті людини. RU: Статья посвящена осмыслению праздника как феномена культуры. Проанализированы существующие научные концепции праздника. На основе анализа автор построила теоретическую модель праздника как олицетворения идеального мира, учитывая все сущностные характеристики, которые отличают его от обыденной жизни. Сущность праздника раскрыта в контексте его соотношения с буднями. Особое внимание автор уделила освещению структурных компонентов праздники, которые поддерживают его статус в культурном бытии человека. EN: The article is devoted to philosophical interpretation of the holiday as a cultural phenomenon. The author analysed the existing concepts and designed the general model of the holiday. The holiday is the form of culture which is the embodiment of the ideal world of a particular activity which should serve to spiritual relaxation and true happiness. It controls and corrects the life of a man and his actions. It brings the element of improvisation in the daily routine. The holiday reflects the ideal imagination of humanity and is the particular form of the world transformation. The objection of restrictions and rules of everyday life; abundance and lavishness of a festive banquet which contradicts to the misery of everyday life; positive festive emotions and feelings being lack in ordinary life; the contrast between the everyday and festive life are the features which define the essence of the holiday as a cultural phenomenon and determine the necessity of its existence in the modern world. Special attention is focused on the structural components of the holiday which define its status in the person’s cultural life and help the participants to experience the holiday atmosphere and plung into the ”perfect” world, the world of their dreams and aspirations. A holiday mask and costume symbolize the person’s “entry” in the special world of the holiday out of his daily routine. The game promotes the person’s temporary escape from his reality, gives the participants of the holiday the feelings of freedom, neutrality and unselfishness and transfers them in the” perfect” world. A festive banquet, tasty food are the holiday properties which are the symbols of abundance and lavishness of the perfect life. A vital part of the holiday is laughter. It makes people be free from certain social duties. Laughter helps people to overcome fear and negative emotions. So the holiday is contrasted with the everyday life as the opportunity to escape from everyday problems. The participants of the holiday wear the most beautiful dresses made for this event, have delicious food and the best win, allow some freedom in their behavior to experience the fullness of life.
Философское осмысление праздника как феномена культуры
Philosophical interpretation of the holiday as a cultural phenomenon
Keywords: свято; будні; маска; костюм; гра; банкет; сміх; праздник; будни; игра; смех; holiday; mask; everyday life; costume; game; banquet; laughter